First Results in new technique of Arthrosc. Button-to-Button repair of PCL avulsion injuries - Thiele, Joern (Orthop J Sports Med, 2016)
AIMS AND OBJECTIVES: The goal of the study was to describe the short time results of our new surgical technique of arthroscopic Button-to-Button fixation for acute tibial posterior cruciate ligament (PCL) avulsion fractures. Concerning clinical and radiographic outcomes, and complication rates. MATERIALS AND METHODS: This prospective study includes patients with an acute tibial avulsion fracture of the PCL. The reduction and fixation was performed all arthroscopic, reduction and suture fixation by Tight Rope ABS and 2 ABS Buttons (Fa. Arthrex). Indication for image-proven displaced tibial PCL avulsion fractures with posterior knee instability of grade II or higher. The mean follow-up period was 6 months. Follow-up assessment included clinical assessment, functional scores, and radiographic evaluation. RESULTS: First Results showed that Patients had better range of motion compared to Patients with an open technique. The postoperative physiotherapy was not limited by the dorsal approach. We have seen no leck of extension after 6 months due to all arthroscopic technique. All fractures achieved union. We have seen no procedure connected complications like wound infections, Button dislocations or nonunions. CONCLUSION: Treatment of tibial PCL avulsion fractures by all arthroscopic Button-to-Button fixation seems to be a successful technique. The benefit with an stable fixation without a dorsal approach helps the postoperative treatment and avoids soft tissue problems , especially limitations of the extension due to Arthrofibrosis and dorsal scar formation. Intermediate and long term results have to prove the clinical results.